Addiction Psychotherapy: Going Beyond Self-Medication - Feingold, Daniel; Tzur Bitan, Dana (Frontiers in Psychiatry, 2022)
Scientific and clinical work concerning the etiology of substance use and addiction has come a long way in the past decades. Current theories highlight the notion that addiction is rooted in deficits in neurobiological and psychological reward mechanisms, but also as a coping-oriented effort to contend with, or "self-medicate", negative emotional experiences. As such, contemporary approaches in the dynamic psychotherapy of addiction highlight the compensatory nature of addiction, encouraging clinicians to detect the mental suffering underlying addiction and promote alternative coping behaviors. In this perspective article, the authors advocate for an integrative approach towards understanding and addressing addiction in psychotherapy, acknowledging its biological, psychological and social aspects. We propose that in addition to the regulatory process of self-medication, in which negative emotions are being suppressed, compulsive substance use may also reflect a substitutive function, in which negative emotions are being 'acted-out' through the use of drugs or alcohol. We suggest an integrative clinical approach which addresses these psychological aspects in a sequential manner and discuss consequent benefits for clinicians and patients working with and through addiction.